Clinical Character of CASPR2 Autoimmune Encephalitis: A Multiple Center Retrospective Study - Qin, Xiaoxiao; Yang, Huajun; Zhu, Fei; Wang, Qun; Shan, Wei (Frontiers in Immunology, 2021)
To examine the clinical characteristics of autoimmune encephalitis associated with the contactin-associated protein-2 (CASPR2) antibody. Medical records of all patients diagnosed with CASPR2 antibody-associated encephalitis were retrospectively analyzed. Data regarding demographic features, neurological symptoms, and signs, laboratory tests, imaging results, treatments, and prognosis were collected. A total of 25 patients aged from 3 to 79 years old were enrolled in this study, with a median age of 43. Eight of 25 (32%) were female, and 17 of 25 (68%) were male. The median age of symptom onset was 42 years old, with the course of the disease from onset to hospital admission ranging from 2 days to 6 months (median was 17 days). Six patients (6/25) had a fever as an onset symptom. During the course of the disease, Cognitive disturbance was the most common symptom, observed in 17 patients (17/25) in total. Six patients (6/25) met the criteria for limbic encephalitis. The epileptic seizure occurred in 3 of the six. Four patients (4/25) had Morvan syndrome. All patients were positive for anti-CASPR2 antibody in cerebrospinal fluid (CSF) or blood. In 9 patients, antibodies were detected only in blood samples, while positive results were limited in CSF in 5 patients. White blood cell (WBC) counts in the CSF were elevated in 8 patients (8/25). In these patients, proteins decreased in 2 and increased in 5. Abnormal electroencephalogram (EEG) activities included slow background activity and epileptic patterns. Abnormal signals in the bilateral hippocampus were detected by magnetic resonance imaging (MRI) in 3 patients presenting cognitive disturbance. In one patient who had limbic encephalitis, increased metabolism of bilateral basal ganglia and the mesial temporal lobe was revealed by PET-CT. Eleven of 15 patients receiving immunotherapy experienced varying degrees of improvement. Relapse occurred in 4 of 25 patients (4/25) after 2 months. We present this retrospective analysis of anti-CASPR antibody-associated encephalitis to identify its clinical features. It is characterized by diverse manifestations involving the central and peripheral nerve systems and a lower relapse rate. Good response and favorable short-term prognosis after treatment was demonstrated. Additional work is necessary to evaluate the long-term prognosis.